Mirror foot : a case report of rare ten toes polydactyly - Sitorus, Gina Yunit J; Putra, Teuku Nanda; Ikhsan, Muhammad; Jannah, Siti Miftahul (Journal of International Surgery and Clinical Medicine, 2024)
Background: A rare congenital abnormality known as "mirror image polydactyly" of the feet is typified by symmetrical duplication of the foot's fingers. According to Fukuzawa et al., only 28 cases—seven of which include treatment records—have been described in the English literature. Mirror foot can arise as a single congenital defect or a component of a hereditary syndrome involving several congenital defects. Methods: Our outpatient department received a referral for a 3-month-old infant who was born with unilateral mirror-image polydactyly of the foot, along with congenital talipes equinovarus (CTEV) and congenital genu recurvatum. A radiographic examination verified that the left foot had nine metatarsals and ten fingers. Five digits were ablation after preaxial duplicates of the first through fourth metatarsals were disarticulated. Results: Rebuilding a functional and aesthetically beautiful foot was the goal of the surgical care of this case, which will help orthopaedic surgeons manage CTEV for serial cast correction. The foot appeared excellent six months following the surgical procedure. The youngster was referred to the pediatric orthopaedic facility in Jakarta after the local orthopaedic department managed the CTEV without incident. Conclusion: Mirror feet are uncommon, and each patient needs treatment specifically designed for them. Coordination across various departments should be pursued to provide patients with the best care possible.